Ensuring success for "Low Yield" students building lives and molding futures - Linton Professional Development Corp.; LPD Video Journal of Education (Salt Lake City, Utah : Linton Professional Development Corp., 1999)
Takes the perspective that the'low yield' student is a child who has great capacity but has not yet realized it. Presents ways to address this situation:'four critical ingredients for high impact schools, the three domains of holistic teaching, the power of teamwork and synergy, core processes that make holistic teaching work'
Program 1. Critical ingredients for high impact schools (36 min.) -- Program 2. Building success through holistic teaching (34 mins)
Featuring Judson Hixson, Ernestine Riggs, and Cheryl Gholar
Keywords: Underachievement; Underachievers; Instructional systems -- Design; Motivation in education